Tracking thermal-induced amorphization of a zeolitic imidazolate framework via synchrotron in situ far-infrared spectroscopy. - Ryder, MR; Bennett, TD; Kelley, CS; Frogley, MD; Cinque, G; Tan, J-C (Royal Society of Chemistry, 2017)
We present the first use of in situ far-infrared spectroscopy to analyze the thermal amorphization of a zeolitic imidazolate framework material. We explain the nature of vibrational motion changes during the amorphization process and reveal new insights into the effect that temperature has on the Zn-N tetrahedra.